MiR-22-3p Regulates Cell Proliferation and Inhibits Cell Apoptosis through Targeting the eIF4EBP3 Gene in Human Cervical Squamous Carcinoma Cells - Lv, Kang-tai (Int J Med Sci, 2018)
Background: MicroRNAs (miRNAs) are non-coding small RNAs that function as negative regulators of gene expression and are involved in tumour biology. The eIF4E-binding proteins (eIF4EBPs) play essential roles in preventing translation initiation and inhibiting protein synthesis at a global or message-specific level in a variety of tumours. Methods: According to comparative miRNA profiles of clinical cervical cancer and non-cancerous cervical tissue specimens, several miRNAs were aberrantly expressed in the cervical cancer samples. C33a and SiHa cell proliferation and apoptosis were detected using methyl thiazolyl tetrazolium (MTT) and flow cytometry assays, respectively. Results: Among the aberrantly expressed miRNAs, miR-22-3p was significantly differentially expressed in cervical cancer tissues and was highly associated with cervical cancer cell growth regulation. In addition, bioinformatic predictions and experimental validation were used to identify whether eIF4E-binding protein 3 (eIF4EBP3) was a direct target of miR-22-3p; eIF4EBP3 protein levels were generally low in the cervical cancer tissues. Furthermore, functional studies revealed that either a miR-22-3p inhibitor or eIF4EBP3 overexpression could induce apoptosis in cervical cancer cells in vitro. Importantly, we found that eIF4EBP3 accumulation could significantly attenuate cervical cancer cell proliferation triggered by a miR-22-3p mimic as well as enhance apoptosis in cervical cancer cells. Conclusion: Taken together, our data provide primary proof that miR-22-3p can induce cervical cancer cell growth at least in part by up-regulating its expression to decrease eIF4EBP3 expression levels; miR-22-3p thus holds promise as a prognostic biomarker and potential therapeutic target for treating cervical cancer.